The Spread of the Shadow Economy as a Moral Dilemma? - Dzemydaitė, Giedrė; Savilionytė, Ieva (Ekonomika, 2018)
The shadow economy remains a significant problem in post-Soviet countries and less economically developed economies. Even though there are a lot of economic and social arguments for the emergence of the shadow economy, it remains the question how much of the shadow economy, as well as an intrinsic willingness to pay taxes, could be explained by social norms, business ethics and illegal business practices that come from the cultural and historical background. This paper focuses on the ethical dilemma and tries to figure out how morality reflects in the tendency to participate in shadow economy. A qualitative approach is applied in this paper to find linkages between moral norms and an acceptance of the shadow economy. This paper supports the idea that people’s backgrounds, their moral norms and close relationships affect how they perceive tax evasion and how much they are willing to participate in such illegal activities.